2004
DOI: 10.1103/physrevlett.93.086104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocality and Short-Range Wetting Phenomena

Abstract: We propose a non-local interfacial model for 3D short-range wetting at planar and non-planar walls. The model is characterized by a binding potential functional depending only on the bulk Ornstein-Zernike correlation function, which arises from different classes of tube-like fluctuations that connect the interface and the substrate. The theory provides a physical explanation for the origin of the effective position-dependent stiffness and binding potential in approximate local theories, and also obeys the nece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 18 publications
(25 reference statements)
5
99
0
Order By: Relevance
“…The simplest classical version, (7), is recovered if γ FJ = 0. For flat substrates the Hamiltonian of Fisher and Jin is recovered as the low-q limit of the nonlocal functional form proposed by Parry et al, 34 but the latter includes a q dependence in γ (q,ξ IS ). Therefore, the first difference between the two theoretical assumptions would appear as the curvature terms in the expansion γ LV (q) + γ (q,ξ IS ) ≈ γ 0 + γ FJ e −λξ IS + (κ + κ(ξ IS ))q 2 + · · ·.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest classical version, (7), is recovered if γ FJ = 0. For flat substrates the Hamiltonian of Fisher and Jin is recovered as the low-q limit of the nonlocal functional form proposed by Parry et al, 34 but the latter includes a q dependence in γ (q,ξ IS ). Therefore, the first difference between the two theoretical assumptions would appear as the curvature terms in the expansion γ LV (q) + γ (q,ξ IS ) ≈ γ 0 + γ FJ e −λξ IS + (κ + κ(ξ IS ))q 2 + · · ·.…”
Section: Theorymentioning
confidence: 99%
“…(15) and (16), in terms of γ LV (q) and γ (q,ξ IS ), are more general than the top lines in the same equations, given in terms of the local function of ξ (x,y) and its derivatives. Strictly nonlocal interfacial Hamiltonians, as proposed by Parry and 085401-4 coworkers, 34 include double integrals over the surface, like (18) where a kernel function K(|R 1 − R 2 |) links the functional dependence at two points of the interface, with a generic function S(ξ ). The expansion of (16).…”
Section: Theorymentioning
confidence: 99%
“…For liquid interfaces, where surface tension dominates, the situation is more complex. From a theoretical point of view, the influence of capillary fluctuations on wetting phenomena has attracted much attention as it could lead to nonuniversal wetting behavior with critical exponents depending explicitly on temperature [7,8]. Experimentally, the observation of this entropic repulsion in typical liquid layers is challenging, but some observations have shown that a correct description of adsorption isotherms of molecularly thin films could be achieved if one takes the entropic interaction into account [9][10][11][12].…”
mentioning
confidence: 99%
“…Further, for the Ising universality class, the wetting parameter ! k B T= 4 2 takes the value 0:8 close to bulk criticality [2,8]. Using results of renormalization group (RG) theory for complete wetting [27,28], which incorporates thermal fluctuation effects, we derive that the mean-squared width of the confined interface depends linearly on the wetting layer thickness [29],…”
mentioning
confidence: 99%
“…In the wetting context, a long-standing problem, regarding the order of the transition in three-dimensional systems, has been recently solved [23]. The original renormalizationgroup calculations led to the prediction of non-universal results in blatant disagreement with computational studies [24] and experiments [25], both of which yield a meanfield-like second-order phase transition.…”
mentioning
confidence: 99%